The Governance Path of Urban–Rural Integration in Changing Urban–Rural Relationships in the Metropolitan Area: A Case Study of Wuhan, China - Youxu Zheng; Jiangdi Tan; Yaping Huang; Zhiyong Wang (Land, 2022)
Since the founding of the country, China’s urban–rural relations have experienced four stages: differentiation, opposition, coordination, and equivalence. The scope of rural research has expanded from individual villages to group relations, and the research content also tends to the urban–rural integration trend of factor flow. In the context of New Urbanization and the Rural Revitalization Strategies, urban–rural integration is an important starting point to solve urban–rural contradictions, and the metropolitan area is an important spatial carrier to achieving urban–rural integration. Based on investigating the key issues of urban–rural integration and metropolitan governance, this paper constructs a “place function” cognitive framework of urban–rural space in the metropolitan area, and takes Wuhan metropolitan area with its dense rural distribution as an example to recognize the urban–rural spatial characteristics of the metropolitan area scale from six dimensions: spatial structure, land use, settlement distribution, scenic spots, agricultural enterprises, and service facilities. Then, it proposes a spatial development model of the Wuhan metropolitan area of the “point axis structure-, functional area-, resilient network”, and further explores the urban–rural integration path of “planning guidance, policy promotion, and spatial support”.